Wastewater reuse in cooling towers brings success. Issue 2 (March 2016) - Unknown
Abstract : The EU Demoware initiative aims to improve industrial water reuse in Europe. This article looks at Dow's key role in the project and how it developed a system to treat wastewater to a high enough quality to be used in cooling towers.